Traditional therapeutic uses of Marrubium vulgare L. by local populations in the Haddada region (Souk Ahras, Algeria) - Boutabia, Lamia; Telailia, Salah; Menaa, Mohcen (Ethnobotany Research and Applications, 2020)
Background: The White horehound (Marrubium vulgare L.) is a plant of the Lamiaceae family. Native to Europe, North Africa and Asia, it is known for its medicinal and therapeutic properties, which are very interesting given the pharmacological activities of the phytochemicals present in its biological extracts. To this end, an ethnobotanical survey on the species was made in Haddada region of the wilaya of Souk Ahras (extreme northeast of Algeria) in order to know its therapeutic uses by the indigenous populations of three localities of said region. Methods: Data collection was based on ethnobotanical surveys of the inhabitants of local population. A total of 205 people were interviewed in the study area through a survey, prepared beforehand. The assessment of knowledge relating to the use of the plant by local populations was based on seven parameters, namely the sex of the people interviewers and their age, Their family situation, their level of education, the part of the plant used, the methods of preparation and the disease treated. Results: The results indicate a significant variation in use knowledge among the populations of the three studied localities. In addition, gender and age clearly influence the level of knowledge. Women have more knowledge than men about the use of different parts of the white horehound. The most cited therapeutic uses are: wound healing and disinfection, diabetes, high blood pressure and respiratory diseases. The most used parts of the plant are the leaves. The most common modes of use are infusion for internal use and decoction for external use. Conclusion: Given the therapeutic interest of the species, promoting its preservation through rational use becomes a priority action in the global strategy of conservation of plant genetic resources at local and regional scale. Keywords: Marrubium vulgare L. - Ethnobotany - Phytotherapy - Souk Ahras - Algeria.